Allergic Rhinitis in Childhood. A Look at Pathogenesis and Comparison of Treatment Methods (Literature Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Allergic conjunctivitis is a common disease in children, often occurring with allergic rhinitis, and occurring, according to various sources, in 18% of children. Symptoms such as itchy eyes, lacrimation associated with symptoms of allergic rhinitis, difficulty in nasal breathing, rhinorrhea - often cause severe physical and emotional suffering, discomfort, and reduce the quality of life of patients.